Semantic Shifts in Classical and Modern Arabic: A Diachronic Study of Key Lexical Terms / التحولات الدلالية في اللغة العربية الكلاسيكية والحديثة: دراسة تاريخية لمصطلحات معجمية رئيسية - Layla Al-Mansouri (IJAS: International Journal of Arabic Studies, 2025)
This study explores the phenomenon of semantic shifts in the Arabic language, examining key lexical terms that have undergone changes from Classical Arabic to Modern Arabic. The research employs a diachronic approach to trace the historical evolution of meanings and analyze the sociocultural, political, and technological factors influencing these changes. By utilizing classical and modern dictionaries such as Lisan al-Arab, Taj al-‘Arus, and Al-Mu‘jam Al-Wasith, along with textual analysis from literary, historical, and contemporary media sources, this study identifies patterns of semantic change, including amelioration, pejoration, broadening, and narrowing of meaning. The findings reveal that semantic shifts in Arabic occur as a natural response to societal developments and cultural transformations. Terms that were once confined to religious or literary contexts in Classical Arabic have acquired new meanings due to modern advancements and globalization. This research highlights the implications of semantic change for understanding classical and modern Arabic texts, translation challenges, and language education. The study concludes by emphasizing the need for further research using digital corpus analysis and the development of a diachronic Arabic dictionary to systematically document semantic evolution across different historical periods.